Synthesis and Characterization of Some New Metal Complexes of 2-phenyl-2-(p-tolylamino) and 2-phenyl-2-(phenylamino) Acetonitrile Compounds - H. A. Al-Amery, Mohammed; Sattar Meteab, Hamid (Iraqi Journal of Science, 2023)
The synthesis and characterization of new complexes of Cr(III), Fe(III), Co(II), Ni(II), Cu(II) and Zn(II) with bidentate [L1: 2-phenyl-2-(p-tolylamino) acetonitrile] and [L2: 2-phenyl-2-(phenylamino) acetonitrile] ligands has been described. The two ligands were prepared by the reaction of p-toluidine and aniline with benzaldehyde, respectively in the presence of potassium cyanide and acidic medium. The complexes were synthesized by treating an ethanolic solution of the ligand with metal salts in a mole ratio of [1:2] [M:L]. The complexes were characterized by using metal and elemental analyses, electronic spectra, 1H-NMR, 13C-NMR, Thermal Gravimetric Analysis TGA, molar conductivity and magnetic susceptibility. According to the obtained data the probable coordination geometries of metal ions in these complexes were suggested as octahedral. Some complexes were found to be non-electrolyte others were found to be weak electrolyte in ethanol.